2022
DOI: 10.3389/fpubh.2021.784718
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Clinical Significance of PIVKA-II in Hepatitis E Patients

Abstract: Increased protein induced by vitamin K absence or antagonist-II (PIVKA-II) levels had been widely reported in patients with hepatocellular carcinoma (HCC) and chronic hepatitis. However, the role of PIVKA-II in hepatitis E is unclear. The aim of this study was to clarify the changes related with PIVKA-II and its clinical significance in hepatitis E. We enrolled 84 patients with hepatitis E hospitalized in two hospitals from December 2019 to June 2021. The levels of serum PIVKA-II and related serological indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…Even though both AFP and PIVKA-II are useful diagnostic markers for HCC, a previous report found that they may not be a good marker for small HCC nodules less than 2 cm as they have sensitivity of approximately 50% (29). However, they may be used for HCC detection particularly in hepatitis virus-related HCC (22,30). A study from China found similar findings as this study but different cutoff for both AFP and PIVKA-II (31).…”
Section: Discussionsupporting
confidence: 76%
“…Even though both AFP and PIVKA-II are useful diagnostic markers for HCC, a previous report found that they may not be a good marker for small HCC nodules less than 2 cm as they have sensitivity of approximately 50% (29). However, they may be used for HCC detection particularly in hepatitis virus-related HCC (22,30). A study from China found similar findings as this study but different cutoff for both AFP and PIVKA-II (31).…”
Section: Discussionsupporting
confidence: 76%